GATT Issues, Gut Issues - Canlas, Corinne A. (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
The General Agreement on Tariffs and Trade (GATT) finds its theoretical foundation in the economic theory of comparative advantage, from which it draws the set of basic trading principles that it overtly upholds, namely, nondiscrimination, reciprocity, and transparency. In accordance with these principles, GATT sells itself as an agreement that will ensure fair trade through the rationalization of trade barriers and prevention of trade wars between its members. This paper counters such claims, showing how developing countries could suffer from the stipulations of the treaty emerging from the Uruguay Round of GATT negotiations. The purported economic improvements in developing countries under the treaty are highly suspect. GATT makes developing countries vulnerable to potential exploitation by the dominators of the world market. Additionally, profit-driven transnational corporations successfully lobbied for their interests—against those of developing countries—in the GATT negotiating table. The argument against the latest GATT treaty boils down to its effect on agricultural production in developing countries, particularly the Philippines. With a government that has never provided food subsidies or any similar forms of support to its farmers, the Philippines stands to lose from GATT’s imposition against such subsidies in the name of creating a level playing field. The country is in a rush to industrialize in order to become globally competitive, hence it is reducing the portion of its lands dedicated to agriculture. This could lead to the worsening of the country’s dismal state of food security. With this subjection of lands to the terms of market efficiency comes the decreasing possibility of genuine land reform. In light of the country’s ratification of the GATT treaty, the paper insists that after consulting with the affected sectors of society, the Philippine government must prioritize the establishment of national food self-reliance through accelerated implementation of agrarian reform and the endowment of financial support to small farmers.
Keywords: GATT · comparative advantage · Uruguay Round · transnational corporations · Philippines